GIS Contribution for Identification of Accident Black Spots –A Review - Umesh M, Raut; Rajesh K, Dhumal; Ajay D, Nagne; Kale, KV (International Journal of Computer Sciences and Engineering, 2025)
Traffic accidents contributing major death problems due to increase in number of vehicles. Globally, more than 1 million people die each year from traffic crashes and about 25–50 million are injured or permanently wounded. In India, thousands of people are dying due to road accidents. It is a necessary task to reduce accidents by performing analysis and taking pertinent countermeasures.So, identification of accident black spots is an important aspect in accident studies. Accident analysis aim at identification of high rate accidents spots, and safety areas. For proper road accident analysis, use of GIS is important.